2017
DOI: 10.1089/jayao.2016.0067
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Discomfort of Adolescent and Young Adult Hematologic Cancer Survivors

Abstract: This study focuses on body image discomfort (BID) of 50 adolescent and young adult (AYA) hematologic cancer survivors (age range 15-23; 52% males). The study results were obtained through data from a self-report questionnaire: the Body Uneasiness Test. Findings differed according to gender: a greater proportion of females were in the Risk category of impaired body image than males (χ = 5.258, p < 0.05). No significant body image differences were found according to the type of diagnosis or to the length of surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
4
29
0
5
Order By: Relevance
“…On the basis of this framework, we assumed that changes in appearance caused by OCC, and its treatment would lead to differences in internalization and representation between males and females. Previous studies of cancer patients indicated that poor physical function, greater emotional distress, poor psychosocial function, and female gender were negatively associated with body image satisfaction. These patients may also experience altered body image after treatment, although insufficient attention has been devoted to this important topic.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the basis of this framework, we assumed that changes in appearance caused by OCC, and its treatment would lead to differences in internalization and representation between males and females. Previous studies of cancer patients indicated that poor physical function, greater emotional distress, poor psychosocial function, and female gender were negatively associated with body image satisfaction. These patients may also experience altered body image after treatment, although insufficient attention has been devoted to this important topic.…”
Section: Introductionmentioning
confidence: 92%
“…An altered body image in cancer patients is associated with more physical symptoms, depression, lower global health status, more severe symptoms, and impaired psychosocial adjustment . Gender also affects the psychosocial adaptation and body image of cancer patients, in that females report greater psychological disturbances, more changes in appearance, and greater alterations in body image …”
Section: Introductionmentioning
confidence: 99%
“…The extent to which results and clinical implications can be generalised to a broader AYA population with a diverse range of cancers is unclear. Quantitative data have shown AYA body image to worsen as a result of the cancer experience (Bellizzi et al, ), particularly in women (Olsson, Enskär, Steineck, Wilderäng, & Jarfelt, ; Vlachioti, Perdikaris, Megapanou, Sava, & Matziou, ; Zucchetti et al, ). In a Danish study, more than half of AYA patients and survivors reported that cancer had negatively affected their body image, and 45% reported that it negatively affected their feelings of being attractive (Graugaard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, over 40% of childhood cancer survivors develope severe or chronic health conditions such as second malignancies, cardiac and vascular abnormalities, pulmonary complications. Moreover, these effects are always associated with stress, isolation and depression state [2] and body image discomfort [3]. For these reasons, the need for a structured long-term follow-up (LTFU) system, aimed at countering potential health risks and supporting beneficial behaviors among youth survivors, has been widely recognized.…”
Section: Introductionmentioning
confidence: 99%